Fridtjof Nansen [electronic resource] : his life and explorations - Bain, J. Arthur (James Arthur) (New York; Toronto : F.H. Revell, 1897)
"Abridged from the larger work." Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44